2018
DOI: 10.1159/000486791
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophosphamide or Rituximab Treatment of Scleritis and Uveitis for Patients with Granulomatosis with Polyangiitis

Abstract: Purpose: Vision-threatening ocular inflammation can be a devastating complication of granulomatosis with polyangiitis (GPA). Here we performed a retrospective observational study to describe the safety and efficacy of treating scleritis and uveitis with either cyclophosphamide or rituximab in GPA. Methods: A chart review of patients diagnosed with GPA-associated scleritis or uveitis, treated with either cyclophosphamide or rituximab as the final therapy at our clinic, was conducted. A total of 1 year of follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 34 publications
1
16
0
3
Order By: Relevance
“…The EULAR guideline can be applied in ophthalmological context, as studies and case reports showed efficacy in treating ocular inflammation. For instance, a small study [24] of 13 patients (19 eyes) suffering from scleritis, uveitis and/ or peripheral ulcerative keratitis proved that both cyclophosphamide and rituximab induced remission of the inflammation, with most of the treated eyes (79%) preserving or improving vision at follow-up.…”
Section: Treatment Of Ocular Complications In Aavmentioning
confidence: 99%
“…The EULAR guideline can be applied in ophthalmological context, as studies and case reports showed efficacy in treating ocular inflammation. For instance, a small study [24] of 13 patients (19 eyes) suffering from scleritis, uveitis and/ or peripheral ulcerative keratitis proved that both cyclophosphamide and rituximab induced remission of the inflammation, with most of the treated eyes (79%) preserving or improving vision at follow-up.…”
Section: Treatment Of Ocular Complications In Aavmentioning
confidence: 99%
“…A recent study by Ahmed et al confirmed that both CYC and RTX were effective in inducing the remission of GPA-associated scleritis and uveitis. Moreover, RTX appeared to be superior in terms of safety and efficacy, with less need for treatment interruptions and dose adjustments [59]. Along with the systemic treatment, local therapeutic agents such as antibiotic, lubricant and/or steroid containing eye drops, and surgical approaches including dacryocystorhinostomy, ocular surface reconstruction by mucosal or amniotic membrane graft, keratoplasty are also used.…”
Section: Treatmentmentioning
confidence: 99%
“…Rituximab is approved in the treatment of rheumatoid arthritis and granulomatosis with polyangiitis. Ahmed et al [114] observed an efficacy of rituximab alone, without corticosteroid, in 60% of patients (3 of 5 patients), with a mean duration of treatment of 32 months. In Lasave's study [115], 11 patients with posterior refractory uveitis were treated with rituximab alone, without corticosteroid, during a minimal follow-up of 24 months.…”
Section: Rituximabmentioning
confidence: 99%